Sistem Pakar Membangun Kesuksesan Bisnis Ritel Syariah Menggunakan Metode Forward Chaining dan Certainty Factor - Reza Adhitya Budiman; Ilka Zufria; Muhammad Siddik Hasibuan (Journal on Education, 2024)
Sharia Retail Business is a type of business that sells goods with a sharia-based retail system. The increasing number of expert systems made by westerners, it is a challenge to create an expert system that is in accordance with Islamic law. The number of Islamic people who like retail businesses such as Carrefour or Alfamart is a reason to create an expert system about retail business. The expert system was chosen because it makes it easier for users to master the concept of Islamic retail business through a knowledge base that is in accordance with sharia teachings. Regarding forward chaining, what is applied is reasoning based on rules that are made and selected to help users choose facts about retail businesses first that suit them, then conclusions are made on previously selected facts. The certainty factor applied is a method that defines belief in a fact and is used to overcome uncertainty in retail businesses. Sharia is applied to the retail business to make it easier for people to purchase goods in unit quantities. The problem in this study is that it is difficult to ascertain whether a retail transaction is sharia-based or not if only seen from the naked eye, in addition to going to a retail store at a cost, there is another solution, namely implementing an expert system in conducting sharia retail transactions. In conducting Islamic retail transactions, a method or algorithm is needed in building an expert system, this study uses Forward Chainning and Certainty Factor algorithms.